Trend Following Algorithms on India’s Nifty Index - Slivka, Ronald T.; Keswani, Vishal; Li, Xuxiang (Indian Journal of Finance, 2014)
The objective of this technical analysis study was to test the profitability of 80 related trend following algorithms applied to closing prices for India’s Nifty index over periods of rising, falling, mixed trend, and nearly trendless markets. Daily closing prices for the Nifty index were divided into four periods covering trading days from 2005 through 2012. Trend following rules were used that employed no leverage and no short positions. Only investments in the Nifty index or in cash at India’s MIBOR rate were permitted with no transaction costs or dividends assumed. For each period, all 80 related trend following algorithms were statistically examined for significance against return distributions created using a Levich-Thomas bootstrapping process. We conclude from this technical analysis study that the family of 80 algorithms investigated worked well in a sharply declining market, but far less so, or not at all well in markets that were more gradually rising, mixed trend, or nearly trendless.